2015
DOI: 10.1002/ep.12091
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mechanisms of arsenate adsorption onto manganese oxide‐doped aluminum oxide

Abstract: This study focused on the characteristics and mechanisms of arsenate [As(V)] adsorption onto manganese oxide‐doped aluminum oxide. The adsorbent surface was characterized via the Brunauer–Emmett–Teller method, scanning electron microscopy, energy‐dispersive spectroscopy, and X‐ray diffraction. The characterization results indicated a rough and Al‐enriched surface, a surface area of 91.2 m2/g, and an amorphous structure for manganese oxide‐doped aluminum oxide. Most of the As(V) was adsorbed within 1.5 h, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…The values of the correlation coefficient (R 2 ) indicated that the Langmuir model (R 2 ¼ 50.997) was more applicable to the isotherm data than the Freundlich model (R 2 ¼ 50.916-0.938) for the adsorption of As(V) on manganese oxide-doped aluminum oxide. In this study [82], the values of b increased from 0.57 to 0.61 when the temperature was increased from 298 to 318 K. Thus, the Langmuir isotherm parameters confirmed that As(V) adsorption would be more favorable at higher temperatures. The data for adsorption on CEZ revealed that it followed the Langmuir isotherm and the R 2 values determined for both As(III) and As(V) were 0.999 and 0.904, respectively [80].…”
Section: Langmuir Isotherm Modelsupporting
confidence: 70%
See 1 more Smart Citation
“…The values of the correlation coefficient (R 2 ) indicated that the Langmuir model (R 2 ¼ 50.997) was more applicable to the isotherm data than the Freundlich model (R 2 ¼ 50.916-0.938) for the adsorption of As(V) on manganese oxide-doped aluminum oxide. In this study [82], the values of b increased from 0.57 to 0.61 when the temperature was increased from 298 to 318 K. Thus, the Langmuir isotherm parameters confirmed that As(V) adsorption would be more favorable at higher temperatures. The data for adsorption on CEZ revealed that it followed the Langmuir isotherm and the R 2 values determined for both As(III) and As(V) were 0.999 and 0.904, respectively [80].…”
Section: Langmuir Isotherm Modelsupporting
confidence: 70%
“…In addition, As(III) and As(V) adsorption on mosambi peel [116], Arthrobacter sp. biomass [86], As adsorption on copper(II) oxide nanoparticles [140], dried biomass of H. verticilata [108], acid treated Devdaru leaf powder [138], and As(V) adsorption on manganese oxide-doped aluminum oxide [82] and pine leaves [141] fitted well to the pseudo-second order rather than to the pseudo-first order. Most of the kinetic data showed correlation coefficients as R 2 ¼ 0.99.…”
Section: Pseudo-second Order Kinetic Modelmentioning
confidence: 99%
“…In the recent years, many researches have also been conducted to synthesize hybrid adsorbents incorporating Al oxides/hydroxides/oxyhydroxides to remove various anions from water . In our previous study, powdered Al‐based adsorbent (Al–Mn bimetal oxides) is synthesized and its remarkable performance for the removal of As(V) from water is observed . However, this adsorbent is unsuitable for fixed bed reactors because of several drawbacks, such as insufficient mechanical strength and poor hydraulic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The literature studies of the alumina oxide's adsorption concentrate rather on the assimilation of inorganic compounds [15][16][17][18][19][20][21][22][23]. The most frequent aim of the adsorption investigation is the removal of arsenic ions from drinking water [16][17][18].…”
mentioning
confidence: 99%
“…The published processes for the improvement of the effectiveness of adsorption focus on the introduction of various elements or compounds into the adsorbents [18,20,23]. This work presents the enhancement of the absorbability by sufficient preparation techniques.…”
mentioning
confidence: 99%